Study on Spray Characteristics and Spray Droplets Dynamic Behavior of Diesel Engine Fueled by Rapeseed Oil - Sapit Azwan; Razali Mohd. Azahari; Hushim Mohd Faisal; Mohd Ali Mas Fawzi; Khalid Amir; Manshoor Bukhari (MATEC Web of Conferences, 2014)
Fuel-air mixing is important process in diesel combustion. It directly affects the combustion and emission of diesel engine. Biomass fuel needs great help to atomize because the fuel has high viscosity and high distillation temperature. This study investigates the atomization characteristics and droplet dynamic behaviors of diesel engine spray fueled by rapeseed oil (RO). Optical observation of RO spray was carried out using shadowgraph photography technique. Single nano-spark photography technique was used to study the characteristics of the rapeseed oil spray while dual nano-spark shadowgraph technique was used to study the spray droplet behavior. The results show that RO has very poor atomization due to the high viscosity nature of the fuel. This is in agreement with the results from spray droplet dynamic behavior studies that shows due to the high viscosity, the droplets are large in size and travel downward, with very little influence of entrainment effect due to its large kinematic energy.